1993
DOI: 10.1111/j.1471-0528.1993.tb15239.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric studies of ploidy and proliferative indices in the Yorkshire trial of adjuvant progestogen treatment of endometrial cancer

Abstract: Objective To estimate whether flow cytometric indices provide independent measures of prognosis or predict response to prophylactic progestogens in endometrial cancer. Design Endometrial tumour specimens were retrieved and analysed by flow cytometry from 257 women who had been randomly allocated in a previous trial to receive prophylactic progestogen in addition to conventional therapy for endometrial carcinoma. Setting Fourteen district and two teaching hospitals in West Yorkshire. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…higher S-phase fraction in poorly differentiated carcinomas even though the correlation to BrDU was very weak.4 However, in another study no independent predictive value with regard to survival was found when S-phase was corrected for stage and histological grade. 18 The significant difference in Ki-67 expression in tumours from patients with postmenopausal oestrogen therapy compared with tumours from patients who have never received oestrogen treatment supports the belief that tumours from the two groups of patients are of different biology. (It is worth noting that the counting of mitotic figures discriminates the two groups of patients to a much smaller degree than Ki-67.…”
Section: Discussionmentioning
confidence: 83%
“…higher S-phase fraction in poorly differentiated carcinomas even though the correlation to BrDU was very weak.4 However, in another study no independent predictive value with regard to survival was found when S-phase was corrected for stage and histological grade. 18 The significant difference in Ki-67 expression in tumours from patients with postmenopausal oestrogen therapy compared with tumours from patients who have never received oestrogen treatment supports the belief that tumours from the two groups of patients are of different biology. (It is worth noting that the counting of mitotic figures discriminates the two groups of patients to a much smaller degree than Ki-67.…”
Section: Discussionmentioning
confidence: 83%
“…Chromosomal instability leading to structural or numerical aberrations is recognized as an early feature of malignant transformation. These changes occur with high frequency in various malignancies, including endometrial carcinomas, where aneuploidy has been reported in about 20–35% (135, 157, 158). Among endometrial carcinoma patients, measures of DNA ploidy have been found to be significantly correlated with established prognostic factors (159–161).…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…In conclusion, we should be reminded that currently nearly forgotten EC adjuvant therapy with progestins was widely used 30-35 years ago [25]. This change in therapeutic approach may have promoted the switch of certain patient populations to apparently justified but harsher treatment regimens.…”
Section: Introductionmentioning
confidence: 98%